Elementos determinantes na escolha de fornecedores de frutas, legumes e verduras para os varejos locais de Itaqui - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The seek for a healthier life is a global tendency. By this fact, a new consumer class has been introduced to the market, the ones that aiming for healthier foods. The reality found in Itaqui follows this tendency and the local population is also aiming for healthier foods. This new consumer has focusin healthy foods and also an affordable price and good appearance as well; these facts brings more complexity to transactions. Fruits, legumes and vegetables (FLV) retail supply has being done in Itaqui by outside companies, which one sare usually located at farway places and this may result in a high priced and low quality product. Considering this reality, it is important to know the parameters used by the retail to choose these suppliers and what requirements would allow the entrance or permanency of local farmers as FLV suppliers. The "Economy of Transaction Costs" theory was used as a conceptual basis for this research and served as support for the interpretation of how the retail coordinates their actions, which governance mechanisms they adopt and how they regulate their transactions. The analysis was made at the FLV supply chain of three local medium size companies. In order to obtain information, interviews with the managers and farmers, observations and data research was made. The relevant aspects for the supplier choice by the retail agents are: quality of the products, amount and clients satisfaction. Some of the barriers for a supplier partnership are low production capacity, production seasonality, low diversity and "appearance" of the product.
Keywords: Agricultores; Transações; Cadeia de suprimentos; Farmers; Transactions; Supply chain; CNPQ::CIENCIAS AGRARIAS